Molecular-Level Insights into Phosphorus Transformation Mechanisms in Entisol Soils under Multiple Long-Term Fertilization Regimes - Jin Liu; Chaoqun Han; Yuhang Zhao; Dongling Yang; Jianjun Yang; Lei Zheng; Yongfeng Hu; Jumei Li; Peng Sui; Yuanquan Chen; Xiaojun Shi; Yibing Ma (Agronomy, 2022)
Improving phosphorus (P) fertilization strategies benefits mitigating future global P shortage and reducing legacy P loss risk in agricultural lands. In this study, the molecular transformation mechanisms of P in Entisol soils under multiple long-term fertilization regimes including PK; NK; NPK; NPK with pig manure (NPKM); and NPK with rice straw return (NPKS) were investigated by sequential fractionation (SF), synchrotron-based P K-edge X-ray absorption near-edge structure (P-XANES) and solution 31P nuclear magnetic resonance (P-NMR) spectroscopy. Compared with conventional NPK fertilization, a higher accumulation of total P occurred in soils under the PK, NPKM and NPKS treatments. By SF, there were relatively higher contents of NaHCO3-extracted inorganic P (Pi) fractions for the soils under PK (52.5 mg/kg) and NPKM (35.5 mg/kg) fertilization relative to the NPK (23.3 mg/kg) treatment. Consistently, P-XANES analysis revealed that there was a higher proportion of brushite, as a bioavailable P form, in soil under the PK and NPKM treatments compared with the NPK treatment, indicating higher P availability in the Entisol soils under PK and NPKM fertilizations. By P-NMR, long-term PK fertilization resulted in relatively a higher ratio of orthophosphate diesters to orthophosphate monoesters after correction compared with the NPK fertilization, which strongly suggested that N deficiency enhanced the biodegradability of soil organic P (Po) pools, thus providing new molecular-level insights into soil Po transformation. Collectively, these results, obtained from a long-term experimental study, facilitates the comprehensive understanding of P availability and transformation mechanisms in Entisol soils under multiple fertilization regimes, and thus benefits the improvement of fertilization strategies in agricultural soils.